PENGARUH PROGRAM BELT AND ROAD INITIATIVE TERHADAP PEMBANGUNAN JALAN TOL CISUMDAWU JAWA BARAT - Rahminati Rantasori; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Infrastructure is built in order to improve the economy in a country that serves to reduce production numbers, facilitate delivery, and of course save time, and communication between regions that can be resolved quickly. Tiongkok is one of the countries included in the ranks of Indonesia's strategic partners in terms of investment for infrastructure development, especially toll roads. This happened because of various driving factors that Indonesia made to attract these investments.The research conducted with qualitative method particularly the case study to analyze a sequential cases in the field. Data of this research was obtained from the books, journals, official documents and websites that support the hypothesis. The author used interest group level analyze and this research is using liberalism perspective, and dependencya theory.The results of this study show that Tiongkok investment is increasing due to diplomatic efforts to facilitate the entry of Tiongkok investment. Indonesia's diplomatic efforts through BKPM include promotions, work visits, market sounding. As a power of new economy world, Tiongkok initiatives OBOR. Indonesia is as a developing country to become one of member state of OBOR in order to develop its economy. In its implementation, the cooperation of infrastructure between two countries keeps increasing that has effect to the development of Indonesia’s infrastructure significantly, although it can be avoided that there are many obstacles that are needed to be faced. Key words : Economic Diplomacy, Toll Road Construction Infrastructure, Chinese Investment